Effects of food and ethnicity on the pharmacokinetics of venadaparib, a next-generation PARP inhibitor, in healthy Korean, Caucasian, and Chinese male subjects - Kim, Hyun Chul; Yang, Eunsol; Lee, Soyoung; Oh, Jaeseong; Lee, Myongjae; Lee, ChaeEun; Ha, Kyoung Soo; Lee, Won Sik; Jang, In-Jin; Yu, Kyung-Sang (Investigational new drugs, 2024)
Aim Venadaparib is a next-generation poly(ADP-ribose) polymerase inhibitor under development for treating gastric cancer. This study aimed to evaluate the effects of food and ethnicity on the pharmacokinetics (PKs) and safety of venadaparib after a single oral administration in healthy Korean, Caucasian, and Chinese male subjects. Methods In this randomized, open-label, single-dose, two-sequence, two-period, and crossover study, Korean and Caucasian subjects received venadaparib 80 mg in each period (fasted or fed state) with a seven-day washout. In an open-label, single-dose study, Chinese subjects received venadaparib 80 mg only in the fasted state. Serial blood samples were collected up to 72 h post-dosing. Results Twelve subjects from each ethnic group completed the study. The geometric mean ratios (90% confidence intervals) of the maximum plasma concentration (C max ) and area under the plasma concentration-time curve from time zero to the last measurable time point (AUC last ) of venadaparib for the fed to fasted state were 0.82 (0.7457–0.9094) and 1.02 (0.9088–1.1339) in Koreans, and 0.77 (0.6871–0.8609) and 0.96 (0.9017–1.0186) in Caucasians, respectively. No statistically significant differences were observed in C max ( P -value = 0.45) or AUC last ( P -value = 0.30) among the three ethnic groups. A single venadaparib dose was well-tolerated. Conclusion The overall systemic exposure of venadaparib was not affected by the high-fat meal, despite delayed absorption with a decreased C max in the fed state. The PK profiles were comparable among the Korean, Caucasian, and Chinese subjects. A single venadaparib 80 mg dose was safe and well-tolerated in both fasted and fed states.